2011
DOI: 10.3748/wjg.v17.i15.1976
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with irritable bowel syndrome symptoms in hemodialysis patients

Abstract: This study examined potential risk factors for symptoms compatible with IBS in HD patients and identified an association with paracetamol use, post-dialysis potassium level and KDQOL-cognitive function score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
18
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 35 publications
5
18
3
Order By: Relevance
“…It is known that high Hgb levels in HD patients increase the quality of life. In a study, there was a statistically significant relationship between Hgb levels and the symptoms of IBS in HD patients (17). In our study, there was no statistically significant difference between the group with and that without FBDs in terms of mean Hgb levels.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…It is known that high Hgb levels in HD patients increase the quality of life. In a study, there was a statistically significant relationship between Hgb levels and the symptoms of IBS in HD patients (17). In our study, there was no statistically significant difference between the group with and that without FBDs in terms of mean Hgb levels.…”
Section: Discussioncontrasting
confidence: 53%
“…The reason for this may be that female steroids reduce the pain threshold by affecting visceral sensitivity or the serotonin synthesis differences in the central nervous system between genders (21). In a study performed in 196 HD patients by Fiderkiewicz et al (17) IBS was found in 27 (13.8%) patients. This rate was 18% in women and 11% in men, but this difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Japanese study reported only on constipation and showed that constipation was more common among patients undergoing HD compared with continued ambulatory peritoneal dialysis . A summary of the published studies reporting on GI symptoms or GI syndromes in patients with ESRD is presented in Table …”
Section: Discussionmentioning
confidence: 99%